The association between CYP46A1 rs4900442 polymorphism and the risk of Alzheimer's disease: A meta-analysis. (4th May 2016) - Jia, Fengjv; Liu, Zhiguo; Song, Ning; Du, Xixun; Xie, Junxia; Jiang, Hong
Highlights: We performed a meta-analysis to assess CYP46A1 rs4900442 polymorphism in AD. rs4900442 genetic polymorphism was associated with increased risk of AD in the Chinese population. No evidences were detected in Caucasian population. Abstract: Polymorphisms in the CYP46A1 rs4900442 have been controversially associated with increased risk of developing Alzheimer's disease (AD). Therefore, a meta-analysis was performed to assess the possible association between CYP46A1 gene rs4900442 polymorphism and AD. A comprehensive search was conducted to identify all case–control or cohort design studies of the associations between CYP46A1 rs4900442 and AD. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using fixed-effects models. Heterogeneity among studies was evaluated using the I 2 and funnel plot and Egger's test were used to evaluate publication bias. Sensitivity analysis was also performed. Six case-control studies corresponded to the inclusion criteria including 1555 AD cases and 1347 controls for the present meta-analysis. Our results showed that no significant associations between CYP46A1 rs4900442 genetic polymorphism and risk of AD in allele model T vs. C (OR = 0.947, 95%CI = 0.853–1.051), dominant model CC + TC vs. TT (OR = 0.878, 95%CI = 0.734–1.049) and recessive model CC vs. TC + TT (OR = 0.974, 95%CI = 0.826–1.149). Moreover, in the subgroup analysis based on location (Chinese and Caucasian), there was significant association in Chinese population in allele model T vs. C (OR = 0.780, 95%CI = 0.628–0.968), although no obvious associations were found in Caucasian. The meta-analysis suggested that CYP46A1 rs4900442 genetic polymorphism was associated with increased risk of AD in the Chinese population, but no evidences were detected in Caucasian population.